LANGUAGE COURSE MANAGEMENT - Srijono, Djoko (Kajian Linguistik dan Sastra, 2006)
Effective and successful language course needs careful management. Language course management includes four main steps: course design, course promotion, course implementation, and course evaluation. Language course design is a dy- namic and negotiated process between the course manager and the learner. After the negotiation, the objective of the course based on the learnersâ needs can be formulated, the suitable approach is adopted, the course materials, the methods and media, and the course tuition are determined. The role of course promotion is essential to achieve the success of the language course. The course promotion should be interesting, promisisng to attract the learnersâ motivation to join the course. The course designer, the tutor, and administrator sould do their best in serving the learners. To make the bettrment of the language course conducted the course de- signer should conduct learner assessment and course evaluation.Â Key words:Â  Â course management, course design, course promotion, course imple- mentation, and course evaluation.Â